Bevacizumab or laser for aggressive posterior retinopathy of prematurity - Blair, Michael (Taiwan J Ophthalmol, 2018)
PURPOSE: The purpose of this study was to report the rate of reactivation and structural outcome, after the laser or bevacizumab treatment for aggressive posterior retinopathy of prematurity (APROP). METHODS: Retrospective chart review was conducted on consecutive infants with APROP treated with (1) laser or (2) bevacizumab, followed by fluorescein angiography and prophylactic laser to the persistent avascular retina. RESULTS: Thirty-six eyes of 19 patients were included in this study. The mean gestational age was 24.5 weeks with a mean birth weight of 632 g in the bevacizumab group and 24.7 weeks and 777 g in the laser group. Unfavorable outcome occurred in 1 of 22 eyes treated with bevacizumab and in 5 of 14 eyes in the laser group (P = 0.002). Reactivation requiring treatment was common in both groups, 9/22 after bevacizumab and 6/14 after laser (ns). CONCLUSION: Regardless of the initial treatment reactivation requiring retreatment is common in eyes with APROP. The unfavorable structural outcome was significantly more common after initial laser treatment than after initial bevacizumab treatment.